2006
DOI: 10.1038/nature04873
|View full text |Cite
|
Sign up to set email alerts
|

Validating cancer drug targets

Abstract: A cancer drug target is only truly validated by demonstrating that a given therapeutic agent is clinically effective and acts through the target against which it was designed. Nevertheless, it is desirable to declare an early-stage drug target as 'validated' before investing in a full-scale drug discovery programme dedicated to it. Although the outcome of validation studies can guide cancer research programmes, strictly defined universal validation criteria have not been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
78
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(86 citation statements)
references
References 49 publications
1
78
0
1
Order By: Relevance
“…Potential options for genotype-specific anticancer therapies arising from FA pathway inactivation in tumors will require suitable preclinical models, for which stringent and universal validation criteria have not yet been established (47). Various models of FA gene defects have been developed, each of which has certain limitations when used for pharmacogenomic studies.…”
Section: Clinical Translational Advancesmentioning
confidence: 99%
“…Potential options for genotype-specific anticancer therapies arising from FA pathway inactivation in tumors will require suitable preclinical models, for which stringent and universal validation criteria have not yet been established (47). Various models of FA gene defects have been developed, each of which has certain limitations when used for pharmacogenomic studies.…”
Section: Clinical Translational Advancesmentioning
confidence: 99%
“…A análise do nível de expressão de proteínas de um mesmo organismo (e.g., normais, superexpressas, deficientes) pode relevar características estruturais e funcionais que permitam diferenciar tecidos patológicos dos sadios, levando à seleção de alvos para o planejamento de fármacos. 19 No caso de doenças humanas causadas por micro-organismos, uma investigação das principais vias bioquímicas possibilita a identificação de proteínas essenciais para o crescimento e desenvolvimento do micro-organismo alvo (e.g., bactéria, parasita, fungo). Uma análise comparativa dos organismos pode levar, preferencialmente, à seleção de proteínas ausentes no hospedeiro (i.e., específicas para o patógeno) ou então com importantes diferenças estruturais em relação às proteínas que desempenham função análoga em humanos.…”
Section: Seleção Do Alvo Molecularunclassified
“…The study of the molecular biology of cancer has identified several proteins which have potential as targets for new anticancer drugs (Sebolt-Leopold and English, 2006) and, in some cases, laboratory preclinical experiments have provided support that has encouraged the development of drugs directed against these systems. These new agents produce a more selective effect on these cells as they are directed, in principle, specifically to the molecular changes which distinguish cancer cells from normal cells thereby reducing toxicity to normal tissues (Benson et al, 2006). A few drugs to these targets have been evaluated by clinical trials, and a fraction of these have received regulatory approval for use in certain groups of cancer patients (Garber, 2006).…”
mentioning
confidence: 99%
“…A particular class of targets, which have proved to be of value are the proteins involved in signal transduction (Benson et al, 2006). The family of signal transduction proteins that has received the most attention to date are the Epidermal Growth Factor Receptor (EGFR) family, most likely as several of its members are manifestly involved in stimulating tumour growth and concepts of drug action are clear (Yarden and Sliwkowski, 2001;Mosesson and Yarden, 2004;Warren and Landgraf, 2006).…”
mentioning
confidence: 99%